Impact of bisphenol A on cell viability and inflammatory cytokine production in human cervical epithelial cells - Tantengco, Ourlad Alzeus G.; Vidal, Manuel S.; Bento, Giovana Fernanda Cosi [UNESP]; Menon, Ramkumar (Wiley, 2023)
Problem: An intact cervix is a barrier that prevents pathogenic bacteria from invading the uterine and amniotic cavity during pregnancy. Its disruption is associated with ascending infection and adverse pregnancy outcomes. This study analyzed the effects of bisphenol A (BPA), a chemical used in plastics manufacturing, on cell death and inflammation in cervical epithelial cells. Methods: Ectocervical epithelial (ecto) and endocervical epithelial (endo) cells were treated with 100 ng/mL and 300 ng/mL of BPA for 48 h. The cells were subjected to flow cytometry using annexin V and propidium iodide to determine apoptosis and necrosis, cell cycle analysis, and ELISA to determine the levels of inflammatory cytokines (IL-6, IL-8, and IL-10). Results: Low-dose and high-dose BPA significantly increased the live ecto cell population dose-dependently. BPA did not have any noticeable effect on cell cycle progression in either cell type. BPA treatment also decreased the apoptotic ecto and endo cell population dose-dependently. Lastly, high dose BPA significantly increased IL-6 in ecto and endo cells. However, IL-8 and IL-10 were not affected by BPA treatments. Conclusion: Chemical exposure damage to the cervix can lead to adverse pregnancy outcomes. Our study showed that the BPA concentrations reported in pregnant subjects do not induce cervical cell toxicity. The decrease in apoptosis and increase in live cells may be a compensatory mechanism to preserve the integrity of the cervical epithelial layer.
Keywords: cervix; endocrine disruptor; inflammation; pregnancy; preterm birth; reproductive toxicology